Illuminating how identities, stereotypes and inequalities matter through gender studies - Farris, Demetrea Nicole; Davis, Maryann; Compton, D'Lane R. (D'Lane Rebecca), 1977- (Springer, 2014)
This collection highlights and extends contemporary women's and gender studies by presenting theoretical analyses and innovative research conceptualizations, applications and methodologies via a diverse variety of popular-in-the-classroom topics, such as changing masculinities; comedic/dramatic portrayals of ethnicity and discrimination; stigma and differences within mainstream media gender stereotypes; intersections of gendered and sexual identities in social media and fundamental institutions. These topics emphasize relevant issues and nuances within popular culture, identities and perception.